Macromolecular Engineering 2022
DOI: 10.1002/9783527815562.mme0058
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Properties of Thin Polymer Films

Abstract: Rapid industrial processes often freeze polymers in nonequilibrium conformations, which, in turn, cause material properties that are significantly different from the predictions of equilibrium theories. Such deviations in properties may introduce enhanced material performance. Thus, by choosing appropriate processing pathways, we potentially can control macroscopic properties and performance of polymers. However, due to our current lack of fundamental understanding of the behavior of nonequilibrated polymers, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Polymers, due to their long chains, are an entropy-dominated system that will always try to attain a state where it can minimize the free energy. However, while processing the polymers for specific needs, techniques like extrusion align chains, which trap the polymer in a nonequilibrium state. ,,, Depending on the energy available, the polymer will gradually try to achieve its equilibrium state. In the context of thin polymer films, a similar effect is observed.…”
Section: Relevant Aspects In Confined Glassy Polymer Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers, due to their long chains, are an entropy-dominated system that will always try to attain a state where it can minimize the free energy. However, while processing the polymers for specific needs, techniques like extrusion align chains, which trap the polymer in a nonequilibrium state. ,,, Depending on the energy available, the polymer will gradually try to achieve its equilibrium state. In the context of thin polymer films, a similar effect is observed.…”
Section: Relevant Aspects In Confined Glassy Polymer Filmsmentioning
confidence: 99%
“…In such a state, the interfaces start playing a much more prominent role in deciding the properties of polymers, , such as the glass transition temperature ( T g ), viscosity, modulus (stiffness), and relaxation. Among those, T g in thin supported glassy polymer films gained considerable attention since its first observation by Keddie et al The idea behind such an observation has been propagated primarily from a liquid-like enhanced mobility film surface to a sluggish mobility substrate interface, depending on the interaction between the polymer–substrate pair, further extended toward gradient mobility along film thickness. , Advancement in this field of research further enlightens exotic nonequilibrium phenomena, , such as irreversible adsorption and molecular recoiling stress or residual stress ,, related to polymer chain conformations. Since glass transition is a phenomenon accompanied by several orders of magnitude changes in viscosity and is expected to be related to the viscoelasticity of the glass, the above scenarios certainly impose paramount importance in exploring and accounting for capabilities of mechano-rheological characterization of thin nanoconfined glassy polymer films.…”
Section: Introductory Overviewmentioning
confidence: 99%
“…Thanks to this analysis, we can now assess the contribution of other parameters that can be tuned during processing. Previous work has shown that the spinning rate has a significant role in the processing-induced nonequilibrium behavior of thin polymer films. ,, Films with constant thicknesses, but prepared with different rotation rates, revealed residual mechanical stresses that differ by orders of magnitude. , Higher rates correspond to shorter time scales over which the polymer system can equilibrate, leading to larger residual mechanical stresses. , Interestingly, such preparation-induced mechanical stresses manifest in macroscopic properties like viscosity, elastic modulus, and creep behavior . Such control over the nonequilibrium properties of a given thickness suggests that the processing-induced behavior of polymer films is not a function of thickness but is a function of the molecular perturbations introduced by processing.…”
mentioning
confidence: 97%
“…4,16 Interestingly, such preparation-induced mechanical stresses manifest in macroscopic properties like viscosity, elastic modulus, and creep behavior. 27 Such control over the nonequilibrium properties of a given thickness suggests that the processing-induced behavior of polymer films is not a function of thickness but is a function of the molecular perturbations introduced by processing. With these ideas in mind, we considered what could be the right observable for probing molecular perturbations underlying the mechanical residual stresses.…”
mentioning
confidence: 99%
See 1 more Smart Citation